Readers' guide to periodical literature 2011 - 20160731 frey50 (New York H. W. Wilson, 2012)
This is a cumulative author-subject index to English language periodicals of general interest. The main body of the Index consists of subject and author entries to periodical articles arranged in one alphabet. In addition there is a listing of citations to book reviews following the main body of the Index.
Keywords: Periodical literature - author index - 2011. -- Periodical literature - subject index - 2011.